Special Education Teachers’ Knowledge on Inclusive Education Provision in Nepal - Neupane, Nam Raj; Niure, Dhruba Prasad (ILAM इलम, 2023)
The study aimed to explore the knowledge and awareness of the teachers of special schools regarding the inclusive education policy of Nepal. The study was guided by a qualitative paradigm followed by a descriptive design. Five special schools from Kathmandu Valley were taken as sample schools, of which two were chosen from Kathmandu, two from Bhaktapur and one from Lalitpur districts by the convenience sampling method. Similarly, 15 teachers (three teachers from each school) were selected purposefully. The semi-structured interview protocol was administered to the teachers for collating in-depth information. Teachers were found to lack knowledge of inclusive education policy. Their acquaintance and familiarity with components of the inclusive education policy, such as limited knowledge of disability and structural provision, was found lacking, whereas they were quite familiar with the disabled-friendly environment and the educational rights of students with disabilities. Their knowledge of functional assessment was very poor compared to other components of the policy. Similarly, teachers lack knowledge and understanding of inclusive school culture, as mentioned in the inclusive education policy of Nepal.